High dose magnesium supplementation effects on 400m sprint performance and metabolism - Chen, C. H.; Smith, R. W.; Jang, J. T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Matwejews (1972) proposed the sports training `period` he divided it into preparation periods, specific training periods, and a competition period. This type of process allow athlete to reach their best physical condition in specific period and maintain it through the competition period. It is still unclear whether other training methods can push the athlete to breakthrough through to new levels of peak performance. Therefore, the aim of this study was to observe the effects of short term and high doses magnesium supplementation before high intensity interval training on performance and metabolism for 400 m runners Methods Two tests were investigated in this study. The first was 400m test (pre and post test), the second was a training test (the 1st and 3rd day). The training program consisted of a high intermittent mode on the 1st and 3rd day and a continuous run on the 2nd day. The intermittent and continuous workload were set 90% (3x3x20s) and 50% (15min) of the individuals best performance time; each athlete took 400 mg magnesium with 200ml water and warmed up for 30mins before each of the three days of training sessions. Results During the training test (Tr-1 and Tr-3), blood lactate and NH3 concentrations decreased after Tr-3 (p>.05). During the 400m test, three subjects improved their range of speed performance by 0.01-1.80 s posttest; two subjects increased their range of speed performance by 0.21 and 0.54 s. Only one subject showed no increase in range of speed performance but still maintained pretest results. Discussion During the training test, blood lactate concentration and NH3 were decreased. Lukaski (1983) explained blood lactate concentration decreased by saying that magnesium stimulates the two-phosphoglycerate (2, 3-diphosphoglycerate, 2, 3-DPG) enzymes, while increasing red blood cells to release oxygen to work the application of muscle tissue. Bertschat et al.(1986) study indicated when looking at marathoners who supplemented with magnesium showed a significant reduction in competition protein degradation, and NH3 generated reduced. Hypothetically speaking, this may be due to the reduction of neonatal sugar resulting in a reducted its metabolites NH3, in addition to magnesium and is also involved in cell ammonia (ammonia) to eliminate an important enzyme. Golf et al.(1998) pointed out that triathlon competitors after four weeks of added magnesium reduced their race times. Comparison to this study only three subjects improved their 400m results, this may be due to the supplement ingestion time being only 3 days.